Students' affordance of teleologic explanations and antrhropomorphic language in eliciting concepts in physics - Romiro Gordo Bautista (OmniaScience, 2015)
This study ascertains the students' affordance of teleologic explanations and anthropomorphic language in eliciting concepts in Physics as influenced by their age and learning exposure and experience. Using Explicative-Reductive Method of Descriptive Research, this study focused on the determinants of students' affordance of teleologic-anthropomorphic reasoning to select concepts in Physics: Kinematics, Dynamics, Statics and Introduction to Thermodynamics.  It was found out that the respondents had intermittently committed teleologic-anthropomorphic languages across age and nature of their secondary education. Furthermore, teleologic-anthropomorphic languages were found correctible by classroom interventions as indicated by the test results on age and curricular exposure.